African Modernism: A Comparative Study of Resistance in the Modernist Art of Nigeria and South Africa. Issue 2 (2nd September 2019) - James, Sule Ameh
Abstract : This paper adopts comparative analysis as a classic art historic methodology for the study of resistance in the art during African modernism in Nigeria and South Africa. Other methodologies that are combined in this paper as an underlying paradigm and analytical methods include formal analysis and cultural history. While the comparative analysis is adopted to interrogate commonalities for similarities and differences regarding African modernism and resistance art produced by some modern artists in Nigeria and South Africa, the formal analysis is articulated to focus on gathering information exclusively from the visual elements of each work and the meanings conveyed to viewers and the cultural history method is adopted to narrate a history that is recalled or invoked in each art. The comparison reveals that, while the South African artists were engaged in resistance art which convey political commentaries, Nigeria artists were engaged in resistance art that relayed cultural commentaries.